The Role And Responsibility Of Public Notary To The Agreement Of Bequest Which Made (Legal Studies of the Revoked Bequest to the Children by Their Parents) - Devi Sulastyo Pinuji Wibawa; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
A bequest is a gift from someone to others in the end of his/ her life. A bequest can be given to anybody, including friend, relative, or the biological children. A bequest is included in the “free” agreement (om niet). It means there must be an achievement for one side, while another one doesn’t need giving contra-achievement as a reward. This kind of agreement is also called as “unilateral” as a contrary of “bilateral” agreement. Generally, the agreement has feedback, as commonly there should be the one who undertakes an achievement as he/she will receive a contra-achievement. The definition above is according to the content of paragraph 1666 of the Book of Civil Law, which explains that bequest cannot be revoked. Contrary to the paragraph 212 of the Compilation of Islamic Law that explains that parents’ bequest to their children can be revoked. Which law should be taken as a fundamental law to answer this case? Here, the role and responsibilities of a public notary are very needed to solve the case.Keywords: Bequest; Role; Responsibility; Public Notary.